Bone Scan "Hot Spot" at the Superior Lateral Orbital Margin Fronto-zygomatic Suture Uptake Characterized with Tc-99m MDP SPECT/CT - S. Thang; A. E. H Tan; A. S. W Goh (World Journal of Nuclear Medicine)
Findings of a solitary "hot spot" at the superior lateral orbital margin on bone scan scintigraphy is not uncommonly seen, and is often dismissed as a benign lesion. However, the exact etiology is indeterminate. We present two cases in which hybrid single photon emission computed tomography/computed tomography imaging was able to characterize and localize this uptake, demonstrating correlation to the right fronto-zygomatic suture.